2018
DOI: 10.3892/mco.2018.1605
|View full text |Cite
|
Sign up to set email alerts
|

Definition of fields margins for palliative�radiotherapy of pancreatic carcinoma

Abstract: The present study aimed to provide practical guidelines for palliative treatment of advanced carcinoma of the pancreas (CAP) with the 2D technique. Fifteen patients with locally advanced CAP consecutively treated with radiation therapy at the Radiation Oncology Center, Research and Care Foundation ‘Giovanni Paolo II’ (Campobasso, Italy) underwent computed tomography simulation in supine position. Definition of the clinical target volume (CTV) included the head and body of the pancreas, and the retropancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a previous study, we observed that with 2D-SRT, it is possible to meet the current standard dose-volume constraints ( 7 ) only by using lower total doses (30–36 Gy) ( 11 ). In a subsequent study, we defined the optimal fields size for involved-field irradiation of CaP with 2D-SRT technique ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we observed that with 2D-SRT, it is possible to meet the current standard dose-volume constraints ( 7 ) only by using lower total doses (30–36 Gy) ( 11 ). In a subsequent study, we defined the optimal fields size for involved-field irradiation of CaP with 2D-SRT technique ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous analysis ( 5 ), a box-technique based on standard fields was tested. In short, the treatment was planned as follows: i) Standard fields were placed in reference to anatomical structures visible on X-ray images (vertebrae and the duodenum.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, we aimed at providing convenient 2D PCa target delineation tools. In the last years, our team worked on the optimization of 2D-RT in palliative treatments (33)(34)(35). Worth noting is that 2D-RT is still in use in several centers in the world.…”
Section: Treatment Machine ------------------------------------------mentioning
confidence: 99%